Analisis Teori Pilihan Rasional Terhadap Transformasi Madrasah - .., Rosidin (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Madrasa transformation from time to time is based on rational choice which decisioned by leaders, managers, and society. Within the perspective of RCT, that rational choice prefer to the economic concept of making profis and inhibiting loss. As the transformation of the earlier educational institution, Madrasa Nizhamiyah depicts rational choice from its historical background, implemented educational practices, qualifiation of its graduates, andsociety responses towards it. Rational choice which generally bases madrasa transformation in Indonesia is heterogeneous. It shows from non-cooperative action with the government (madrasa in the era of colonization); cooperative action with the government (madrasa in the era of the old order); cooperative action with society needs and working world (madrasa in the era of the new order) and the inclusive-predictive action with the world development (madrasa in the era of reformation and globalization).Keywords: Transformation, Madrasa, RCT, Rational Choice